Mineralogy and Geochemistry of Agates from Paleoproterozoic Volcanic Rocks of the Karelian Craton, Southeast Fennoscandia (Russia) - Evgeniya N. Svetova; Sergei A. Svetov (Minerals, 2020)
Agates of Paleoproterozoic volcanics (2100−1920 Ma) within the Onega Basin (Karelian Craton, Southeast Fennoscandia) were studied using optical and scanning electron microscopy, X-ray powder diffraction, X-ray fluorescence spectrometry XRF, laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), and C-O isotope analysis. Agate mineralization is widespread in the lavas gas vesicles, inter-pillow space of basalts, picrobasalts, basaltic andesites, as well as agglomerate tuffs. Agates are characterized by fine and coarse banding concentric zoning; moss, spotted, veinlet, and poor-fancy texture types were identified. Agate mineralization is represented by silicates, oxides, and hydroxides, carbonates, phosphates, sulfides, and sulfates. Among the silica minerals in agates only chalcedony, quartz and quartzine were found. The parameters of the quartz structure according to the X-ray diffraction data (well-develops reflections (212), (203), (301), large crystallite sizes (Cs 710–1050 Å) and crystallinity index (CI 7.8–10.3) give evidence of multi-stage silica minerals recrystallization due to a metamorphic (thermal) effect. The decreasing trend of trace element concentration in the banded agates from the outer zone to the core suggests a chemical purification process during crystallization. C-O isotope characteristic of agate-associated calcite reflects primary magmatic origin with the influence of hydrothermal activity and/or low-thermal meteoric fluids. Agates were formed under low PT-parameters and related to hydrothermal activity on the first stage of Svecofenian orogeny within 1780−1730 Ma. Thus, it can be believed that the temporal gap between continental flood basalts outflow and agate formation is about 190 Ma.